Determinants of debt maturity structure for public and private debt securities in Malaysia and Singapore - Abdul Wahab, Noor Maimun (2019)
This thesis attempts to meet four main objectives. Firstly, to examine the firm and country specific as determinants for debt maturity structure. Secondly, to examine worldwide governance indicators as new potential determinants for debt maturity structure. Thirdly, to examine factors that caused decision on debt maturity structure to be different across time and lastly, to examine determinants for adjustment of speed for debt maturity structure. All the aforesaid objectives are examined specifically on public and private debt securities in Malaysia and Singapore. The data for all the variables used in this study are collected from World Bank, Thomson Reuters Datastream, Bank Negara Malaysia, and Monetary Authority of Singapore over the period of 1996 to 2016. Altogether data of this study consist of 1,157 listed firms in Malaysia and Singapore. Two-step system generalized method of moment are employed in this study so that the four main objectives of this study are achieved. This study shows that magnitude of determinants which are examined in this study pertaining to issue in debt maturity structure such as determinants for debt maturity structure, factors that influence decision for debt maturity structure to be different across time, and determinants for adjustment of speed are contingent across type of debt securities issued by firms and also country that issued type of debt securities. This study finds that credit ratings is better in explaining determinants for debt maturity structure of public and private debt securities in Singapore whilst worldwide governance indicators are more robust in explaining determinants for debt maturity structure of public and private debt securities in Malaysia as compared to Singapore. In addition, government debt maturity structure plays vital role in affecting decision for debt maturity structure of public and private debt in both countries to be different across time. The worldwide governance indicators, firm and country specific factors are better in affecting adjustment of speed for debt maturity structure of public debt in Malaysia. In short, it is crucial for the firms to maintain a good quality of their firms and the government to ensure the development of debt market, increase the benefit of corporate taxation and maintain the effectiveness of the country governance so that it can assist firms in controlling and stimulating the demand for long-term public and private debt, planning in finding the right time to issue long-term public and private debt securities and quickly adjust their current public and private debt securities in achieving its optimal public and private debt maturity structure. Having long-term public and private debt securities as sources of financing create an opportunity for firms to expand their business worldwide, provide firms with conducive and healthy business environment and in due time contributes to realisation of good economic growth and steadiness in the firms’ business cycle.